2008
DOI: 10.1007/s11709-008-0009-7
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional consolidation of over-consolidated soil under time-dependent loading

Abstract: The problem of one-dimensional consolidation of over-consolidated saturated soil under time-dependent loading was studied based on semi-analytical method. The relevant computer code was developed by FORTRAN programming, and one-dimensional consolidation behavior of over-consolidated soil was investigated. It is shown that, unlike this described by traditional Terzaghi's consolidation theory, the rate of excess pore water pressure dissipation is different from that of settlement developing. The magnitude of loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The analytical solutions of equation (12), with the above conditions, have been developed by Schiffman & Stein (1970), Lee et al (1992), Xie & Pan (1995) and Zhu & Yin (1999) among others.…”
Section: Uncoupled and Coupled 1d Consolidation Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The analytical solutions of equation (12), with the above conditions, have been developed by Schiffman & Stein (1970), Lee et al (1992), Xie & Pan (1995) and Zhu & Yin (1999) among others.…”
Section: Uncoupled and Coupled 1d Consolidation Theoriesmentioning
confidence: 99%
“…The compressibility of the soil layer m v also plays an important role in the rate of consolidation. Xie & Pan (1995) further developed an analytical solution for a layered system under time-dependent loading. Pyrah (1996) showed that the 1D consolidation behaviour of layered soils consisting of two layers with the same value of the c v , but different k and m v were quite different.…”
Section: Introductionmentioning
confidence: 99%
“…Where it is assumed that soil particles are incompressible (dVs = 0). The change in the void volume dVv over change in time t is given by Equation 6.…”
Section: Idealization Of One-dimensional Consolidation Of Stabilized mentioning
confidence: 99%
“…Recent advancement of mathematical modelling in geomechanics has seen the development of numerous published research works of one-dimensional consolidation of soils by analytical and numerical methods [1][2][3][4][5][6][7][8][9][10][11][12][13]. Despite of that, not many analytical and numerical solutions that solved one-dimensional consolidation problem of stabilized peat were found in the literature of geomechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Olson 5 solved the radial and vertical consolidation of soil under construction load. Xie et al 6,7 developed the 1D nonlinear consolidation theory of single-layer soil and double-layered soil under linear loading on the premise that the consolidation coefficient remains unchanged. Since then, more practical factors have been considered by researchers, such as nonlinear deformation, 8 viscoelastic deformation, 9,10 and load mode, 11 which further enriches and develops the 1D consolidation theory of soft soils.…”
Section: Introductionmentioning
confidence: 99%